THE DIFFERENCES IN INTERPRETATION OF THE HADITH: A Study of The Hadith al-Jannatu tahta Aqdam al-Ummahat - Huda, Miftahul (RIWAYAH, 2022)
The study of the differences in the interpretation of the hadith about heaven under the soles of the mother’s feet, aims to examine and analyze the differences in views and debates of the scholars as well as the method of understanding the hadith on heaven under the soles of the mother’s feet (al-jannatu tahta aqdam al-ummahat) contextually. In this study, the method used is qualitative literary study with an analytic-descriptive approach. As for the data analysis using qualitative descriptive analytics, namely describing and analyzing the hadith about al-jannatu tahta aqdam al-ummahat. The results of this study indicate that the status of the hadith about heaven under the soles of the mother’s feet gives rise to two statuses, namely authentic and dhaif. As narrated from Mu’awiyah bin Jahimah, he concluded that the hadith had the status of authentic. Whereas what was narrated by Anas bin Malik with a different path and proof, is declared to have the status of dhaif. The debate of hadith scholars in understanding this hadith is more directed at disputes about hadith narrations with various methods and approaches used, namely the sanad, narrator, and language methods. From the different views of scholars regarding this hadith, it does not lead to the substance of the hadith in question, which commands to do good to parents. This hadith positions a woman (mother) is in Islam as a highly glorified figure.[Kajian mengenai perbedaan dalam penafisran hadis tentang surga di bawah telapak kaki ibu, bertujuan untuk mengkaji dan menganalisa perbedaan pandangan dan perdebatan para ulama serta metode memahami hadis surga di bawah telapak kaki ibu (al-jannatu tahta aqdam al-ummahat) secara kontekstual. Dalam penelitian ini metode yang digunakan yaitu kualitatif bersifat studi kepustakaan dengan pendekatan desktiptif analitik. Adapun analisis data menggunakan kualitatif deskriptif analitik yaitu mendeskripsikan dan menganalisis hadis tentang surga di bawah telapak kaki ibu (al-jannatu tahta aqdam al-ummahat). Hasil penelitian ini menunjukkan bahwa status hadis tentang surga dibawah telapak kaki Ibu menimbulkan dua status yaitu shahih dan dhaif. Seperti yang diriwayatkan dari Mu’awiyah bin Jahimah, ia menyimpulkan bahwa hadis tersebut berstatus shahih. Sedangkan yang diriwayatkan oleh Anas bin Malik dengan jalur dan hujjah berbeda, yaitu dinyatakan berstatus dhaif. Perdebatan para ulama hadis dalam memahami hadis ini lebih mengarah pada perselisihan riwayat hadis dengan berbagai metode dan pedekatan yang digunakan yaitu metode sanad, rawi serta bahasa.  Dari perbedaan pandangan para ulama dan cendikiawan mengenai hadis tersebut, tidak mengarah kepada substansi hadis ini yang memerintahkan untuk melakukan berbuat baik kepada orang tua. Hadis ini memposisikan seorang perempuan (ibu) dalam Islam sebagai sosok yang sangat dimuliakan.]